2014
DOI: 10.1371/journal.pone.0086661
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone Binding Protein BiP Prevents Leaf Dehydration-Induced Cellular Homeostasis Disruption

Abstract: BiP overexpression improves leaf water relations during droughts and delays drought-induced leaf senescence. However, whether BiP controls cellular homeostasis under drought conditions or simply delays dehydration-induced leaf senescence as the primary cause for water stress tolerance remains to be determined. To address this issue, we examined the drought-induced transcriptomes of BiP-overexpressing lines and wild-type (WT) lines under similar leaf water potential (ψw) values. In the WT leaves, a ψw reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 63 publications
3
33
0
Order By: Relevance
“…The diverse responses among eight species to drought in autumn (Table ) could be related to species‐specific physiological response mechanisms to environmental stresses, and the molecular and physiological responses to drought stress by gene regulation on plant hormones and stress‐shock proteins (Carvalho et al. ). Species that are less drought tolerant (e.g., white ash, maples, and black birch; Pääkkönen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse responses among eight species to drought in autumn (Table ) could be related to species‐specific physiological response mechanisms to environmental stresses, and the molecular and physiological responses to drought stress by gene regulation on plant hormones and stress‐shock proteins (Carvalho et al. ). Species that are less drought tolerant (e.g., white ash, maples, and black birch; Pääkkönen et al.…”
Section: Discussionmentioning
confidence: 99%
“…We found that moderate summer heat-stress, summer and fall drought-stress, and summer heavy rain events, all lead to later autumn dormancy, counter to the traditional expectations. Studies on economically important plants (e.g., apples, soybeans, birch) have shown that under moderate heat-or water-stress in summer and fall, associated changes occur in gene-regulated levels of plant hormones and stress-shock proteins (44)(45)(46). The regulatory and physiological changes not only induce greater drought tolerance in plant leaves (47), but also prevent drought-induced cell death in leaves (that would otherwise lead to leaf senescence), and alter photosynthate source-sink relationships among plant organs (roots, stems, and leaves).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon has been little studied (45). Few studies have mentioned either the effects of heat-and drought-stress on fall phenology (45,48) or the potential role of the underlying molecular and physiological mechanisms (44,46). We have an ongoing project of groundbased phenological observations (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All BiP proteins have C-terminal HDEL or KDEL signaling motif, which ensures their retention and function in the ER and an ATP-binding domain near the N-terminus 2 .Across eukaryotes, BiPs are among the most abundant chaperones in the ER and are directly engaged in regulating the unfolded protein response (UPR). Under normal conditions in mammalian cells, BiP binds to and inhibits the three ER stress sensors, protein kinase RNA-like ER kinase (PERK), activating transcription factor 6 (ATF6), and inositol-requiring enzyme 1α (IRE1α) 3,4 . BiP releases the sensors to activate ER-to-nucleus signaling cascades.…”
mentioning
confidence: 99%
“…protein (NRP) and vacuolar processing enzyme [1][2][3][4] . The Arabidopsis, pepper, rice, soybean, and wheat genomes encode three or four BiPs which have been annotated and, extensive studies have revealed that many of these plant BiP proteins play crucial roles in biotic stress resistance and plant innate immunity [5][6][7][8][9] .…”
mentioning
confidence: 99%